Legal regulation of the international road transport of passengers - Đurđev, Dušanka (Zbornik radova Pravnog fakulteta u Novom Sadu, 2018)
Since March 2013 bus and coach passengers have a minimum set of rights when travelling in the European Union. Regulation 181/2011 concerning the rights of passengers in bus and coach transport applies to passengers travelling with regular services that operate at specified intervals along specified routes, with passengers being picked up and set down at predetermined stopping points. Either the boarding or the alighting point must be within the European Union. Some of the Regulation’s provisions are mandatory and apply to all services. The other rights available under the Regulation only apply where the scheduled distance of the service is 250 km or more.